SAT-414 Cytogenetic, Genomic, and Functional Characterization of Pituitary Gonadotrope Cell Lines - Ruf-Zamojski, Frederique (J Endocr Soc, 2019)
Cell lines have been widely used as models to characterize important intracellular and molecular mechanisms. Funding agencies and publishers – including the National Institutes of Health and Nature – have required researchers to authenticate human cell lines to establish their identity. Nevertheless, authentication of human cell lines has been poorly reported, let alone that of nonhuman species [1]. The use of different clones by diverse laboratories may lead to irreproducible results. Moreover, one should not assume that cell lines with the same name actually display identical characteristics, as differences in storage and culturing conditions may promote genomic variability and clonal divergence. In the reproductive field, the LβT2 [2] and αT3-1 [3] cell lines represent invaluable models for studying the regulation of pituitary gonadotropes by gonadotropin releasing hormone (GnRH) and other hormones. Both lines were produced by targeted oncogenesis in transgenic mice, with the LβT2 cells representing developmentally more mature gonadotropes than the αT3-1 cells. To establish a reference for each gonadotrope line, we requested early aliquots from the laboratory that generated them. Authentication by 27-dinucleotide and 9-tetranucleotide short tandem repeat (STR) genotyping was consistent with a mixed C57BL/6J x BALB/cJ genetic background. Spectral karyotyping revealed a variable number of chromosomes amongst cells, a result confirmed by shallow single-cell DNA sequencing in LβT2 cells. Interestingly, STR genotyping of several LβT2 batches obtained regularly throughout the past 20 years in our laboratory as well as in other laboratories identified a strain (#2) with a profile distinct from our reference line (#1). The two lines differed morphologically, with strain #2 exhibiting larger cells and extensions, whereas strain #1 displayed smaller uniform rounded cells. Moreover, the two lines showed variations in basal and GnRH-induced expression of early response and gonadotropin subunit genes. In line #1, under continuous GnRH stimulation, Egr1, Fos, and Lhb transcript levels were higher, whereas time course studies revealed lower Fos expression and no Fshb induction. Under a low-frequency regimen of pulsatile GnRH favoring Fshb induction, line #1 showed higher Egr1 transcript levels, but an absence of Fshb induction. Our results suggests that LβT2 strains exist that differ genetically and in their expression profiles. Our study demonstrates the importance of characterizing gonadotrope cell lines to improve data reproducibility, design and interpretation of gene expression experiments while continuing to use these cell lines that are important models for the study of gonadotrope physiology. [1] Almeida JL et al. PLoS Biol., 2016, 14(6):e1002476. [2] Thomas P et al. Endocrinology, 1996, 137(7): 2979-89. [3] Windle JJ et al. Mol. Endocrinology, 1990, 4(4): 597-603.